L’École Républicaine est-elle le fruit des idées et de valeurs protestantes ? - Anne Ruolt (Recherches en Éducation)
Is the School of Ferry the « daughter of Protestantism »? By comparing the ideas and values of Guizot to their of Buisson, this article raises the question of the relevance of the hypothesis raised by Pastor Paumier » [that] instead of a religion of state, it seems to want to impose a state of irreligion. « Initially, from the writings and reports of AG from Guizot and Gauthey, echoed by President Robert and others members to SEIPPF, when Ferry’s laws were passed, this article recalls the presence of a Protestant-Orthodox current forgotten, who opposed the « three stars » of Buisson, shows that Ferry was not the result of ideas and values of this stream of Protestantism enlivened by the Revival of Geneva. Then, in a second step, the article analyzes the thought of Buisson in a philosophical-theological perspective, and shows from the writings of its founding philosophy, how he has resolutely rejected all of Protestantism orthodox and heterodox to found a « other party » closer to Auguste Comte that of Jean Calvin. The School of Ferry as Buisson is not it rather « daughter of an anti-dogmatic scientism »?